Penerapan Algoritma K-Means Clustering Untuk Pengelompokan Data Pasien Rehabilitasi Narkoba - Ega Yolanda; Suhardi (STMIK Budi Darma, 2023)
Drug abuse’s a serious problem leading to addiction and harmful effects. Rehabilitation aims to save drug addicts and help them lead a normal, physically, and mentally healthy life while improving skills and social relationships. The North Sumatra Province National Narcotics Agency’s responsible for drug prevention, eradication, and rehabilitation. There’re different rehabilitation programs for adolescents and adults, with a